2011
DOI: 10.1002/chem.201100122
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Oligometal Complexation of the Macrocyclic Tris(N2O2) Hexaoxime Ligand

Abstract: A macrocyclic oxime ligand H(6)L, which has an O(6) cavity surrounded by three N(2)O(2) chelate sites, was synthesized and the multistep oligometal complexation behavior was investigated. Upon complexation with zinc(II), the H(6)L ligand afforded two kinds of hexanuclear complexes, L(2)Zn(6) then LZn(6). Each of the complexation steps proceeded highly efficiently. In the latter complex, a Zn(3)(μ(3)-OH) unit was incorporated into the trimetalated ligand, LZn(3). The integrated N(2)O(2) chelate coordination sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…We have already demonstrated that a binding selectivity trend of alkali metal << Zn 2+ < alkaline earth < rare earth metal ions was observed in the shorter L 1 Zn2M system [57] and related complexes [79][80][81][82][83] without chiral auxiliary. If the longer L 4 Zn3M system having a chiral auxiliary also shows a similar selectivity trend, Ba 2+ in the L 4 Zn3Ba can be efficiently replaced by La 3+ .…”
Section: Helicity Inversion By Metal Exchangementioning
confidence: 92%
“…We have already demonstrated that a binding selectivity trend of alkali metal << Zn 2+ < alkaline earth < rare earth metal ions was observed in the shorter L 1 Zn2M system [57] and related complexes [79][80][81][82][83] without chiral auxiliary. If the longer L 4 Zn3M system having a chiral auxiliary also shows a similar selectivity trend, Ba 2+ in the L 4 Zn3Ba can be efficiently replaced by La 3+ .…”
Section: Helicity Inversion By Metal Exchangementioning
confidence: 92%
“…In the crystal structure of the Cu II complex, there were three intermolecular (C8−H8A···O1, C24−H24A···Cl5, and C25−H25A···O8) and one intramolecular (C24−H24A···O3) hydrogen bondings (see Table 4), which played a role in stabilizing the crystal structure of the Cu II complex [72,73]. As a result, the Cu II complex formed a self-assembled infinite two-dimensional supramolecular structure via intermolecular hydrogen bondings, as shown in Figure 3.…”
Section: Supramolecular Interactions and Hirshfeld Surface Analysismentioning
confidence: 99%
“…In the Hirshfeld surface, the existence of strong interactions showed up as red spots [74], while the blue regions were related to weak contacts. The Hirshfeld surface analysis of the Cu II complex is as depicted in Figure 4a (see Table 4), which played a role in stabilizing the crystal structure of the Cu II complex [72,73]. As a result, the Cu II complex formed a self-assembled infinite two-dimensional supramolecular structure via intermolecular hydrogen bondings, as shown in Figure 3.…”
Section: Supramolecular Interactions and Hirshfeld Surface Analysismentioning
confidence: 99%
“…31 This metal cation templated route provided a vast improvement in yield over their previous metal-free attempts to perform 3 + 3 Schiff base condensations of 1,4diformylbenzene-2,3-diol with various diamine linkers. 32 This same method involving templated macrocyclisation was later extended to include various combinations of trivalent lanthanide ions with Zn II , [33][34][35][36][37][38][39][40] Cu II , [41][42][43][44][45][46] Ni II , 47 or Co II centres. 48 Families of triangular macrocyclic complexes containing Zn II , Cu II , and Ni II with a variety of Ln III have been investigated by Brooker et al for their magnetic properties.…”
Section: Introductionmentioning
confidence: 99%